Investigação da produção de hidrogênio por fotofermentação utilizando as bactérias fototróficas Rhodobacter capsulatus e Rhodospirillum rubrum - Ferreira, Gustavo Machado Tottoli (2022)
Hydrogen is a clean energy source said to be able to contain the increase in the Earth's temperature as a result of the exaggerated use of fossil fuels. The production of biological hydrogen by photo fermentation has received much attention in recent years as it offers great potential. In the current research, the biological production of hydrogen by photo fermentation was evaluated using the purple non-sulfur bacteria Rhodobacter capsulatus and Rhodospirillum rubrum cultivated in RCV medium. Lactose from whey permeate, an agro- industrial residue, was used as a carbon source at a starting concentration of 10 g/L. Assays were carried out in 50 mL reactors (small-scale assays) and on a 1.5 L stirred tank reactor (large-scale assays). Initially, the assays carried out on the 50 mL reactors evaluated the use of pure bacterial cultures and were compared with the use of co-cultures formed by different proportions of the species. It was found that the combination of the two species in co-culture formed by the proportion 1:1 (w/w) had shown a maximum productivity of 7.51 mmol H2/L.day. To verify the influence of lactose as a source of carbon, the small-scale assays were replicated using the basal RCV medium as the fermentable medium. The large-scale assays were carried out with medium renewal. Whitin specified time intervals, a fraction of the reaction medium was removed and the reactor was refilled with fresh medium so that the lactose concentration remained approximately in the same range. The medium renewal allowed the removal of organic acids produced as a result of cellular metabolism so that they would not accumulate. The ladder ensured a stable and long-term hydrogen production, reaching a peak productivity of 278.05 mmol H2/L.day. A subsequent assay was carried out employing the same initial conditions without medium renewal. It was observed an accumulation of organic acids resulted in lower peak productivity. The main organic acids detected were lactic, acetic, propionic and butyric acids.